A Case Study of Canine Transmissible Venereal Tumour in Community Dog - Marahatta, S.; Lamsal, K.; Joshi, R. P.; Shrestha, B. (Journal of the Institute of Agriculture and Animal Science, 2020)
Dogs the first animals to be associated with humans have suffered most in unplanned urbanised societies. Community dogs are of serious health and safety problems in developing countries and many are seen suffering in the streets with various problems. Canine transmissible venereal tumour (CTVT), an only transmittable oncogenic disease seen frequently in these community dogs. Veterinary Teaching Hospital (VTH) located at Paklihawa Campus, Institute of Agriculture and Animal Science (IAAS). Tribhuvan University (TU) is the major centre for canine health care in Nepal. A dog was brought with complaints of bleeding from the rear and visible reddish mass. The mass in the genital region was diagnosed to be venereal tumour by cell cytology. For the treatment of CTVT, surgical intervention along with chemotherapy (vincristine @0.025mg/ Kg) was done. To remove the ectoparasite, amitraz bath and ivermectin (0.2mg/Kg) was used. The dog completely recovered and it was returned in its original territory.